Effect of Gd and Co contents on the microstructural, magneto-optical and electrical characteristics of cobalt ferrite (CoFe2O4) nanoparticles. Issue 2 (15th January 2022) - Lu, Yuzheng; Yousaf, Muhammad; Akhtar, Majid Niaz; Noor, Asma; Akbar, Muhammad; Shah, M.A.K. Yousaf; Yan, Senlin; Wang, Faze
Abstract: Rare earth oxides with a trivalent nature play a pivotal role in reinforcing the magneto-optical attributes of spinel ferrite nanoparticles by replacing Fe 3+ ions. In this study, rare earth Gd oxide doped with CoFe2 O4 NPs with a composition of Co1+x Gdx Fe2-2x O4 (x = 0, 0.05, 0.10, and 0.15) were synthesized using sol-gel auto-combustion. The outcome of Gd cations on the physical, magneto-optical and electrical characteristics of the cobalt ferrite NPs were reported. X-ray diffraction (XRD), and Fourier transform infrared (FTIR) investigations confirmed the single-phase cubic crystalline nature and metal ion stretching in the cobalt ferrite synthesized samples. Decreasing drift in the average crystallite and grain sizes (estimated from the XRD patterns and SEM micrographs) and magnetic saturation ( M s ) were examined with the increasing content of Gd oxide and Co ions in the CoFe2 O4 NPs. The optical bandgap of the synthesized samples explains the semiconducting nature of the prepared NPs due to the presence of an E g from 2.13 eV to 2.45 eV in the semiconductor region. The electrical properties of the co-doped samples exhibit a conducting trend in the presence of Gd 3+ ions with the increase of temperature from 298 K to 973 K. DC measurements of the synthesized NPs demonstrated DC conductivity values from 0.1087 S/cm to 0.2676 S/cm at 973 K. Graphical abstract: The room temperature magnetic analysis of Gd and Co doped Cobalt Ferrite (CoFe2 O4 ) NPs using vibrating sample magnetometer; DC conductivity Gd and Co doped Cobalt Ferrite (CoFe2 O4 ) NPs from 298 K to 973 K. Image 1